Monitoring or Colluding? Institutional Investors' Heterogeneity and Environmental Information Disclosure Behavior - Li, Zhengguang; Zhang, Tinghai; Zhao, Xibo; Zhu, Yicheng (Frontiers in Psychology, 2022)
High-quality environmental information disclosure is not only an effective way for the firm to fulfill its environmental responsibility and promote green development, but also an important governance mechanism to reduce the degree of information asymmetry between the firm’s management and shareholders and alleviate the agency conflict. As an important shareholder of a firm, there are two different hypotheses about the influence of institutional investors on firm decision-making and behavior: monitor and collusion. Institutional investors are not homogeneous, and there are significant differences in the impact of different types of institutional investors on firm decision-making and behavior. We divide institutional investors into the stable institutional investors and the unstable institutional investors, using the data of listed firms in China’s A-share heavy pollution industry between 2008 and 2020, this study explores effect of institutional investors’ heterogeneity on environmental information disclosure behavior from the perspective of environmental information disclosure quality. Empirical evidence shows that institutional investors as a whole have a positively significant impact on environmental information disclosure quality. Further analysis shows that the stable institutional investors have positive impact on environmental information disclosure quality compared with the unstable institutional investors. After a series of robustness tests, the conclusion is still valid. The results of this paper show that institutional investors, especially the stable institutional investors, can effectively reduce the degree of information asymmetry, alleviate the agency conflict of the firm, play an active role in corporate governance, strengthen the main responsibility of firm ecological environment protection, and promote the green development of firm. The conclusion of this paper has important reference significance for regulators to formulate policies to improve environmental information disclosure quality and promote green development according to the heterogeneity of institutional investors.